HOW THE HEMOSTASIS LABORATORY CAN HELP CLINICIANS TO MANAGE PATIENTS ON ORAL ANTICOAGULANTS - Armando Tripodi (Mediterranean Journal of Hematology and Infectious Diseases)
Oral anticoagulants are widely used to treat or prevent cardiovascular diseases in millions of patients worldwide. They are the drugs of choice for stroke prevention and systemic embolism in patients with non-valvular atrial fibrillation and prosthetic heart valves, as well as for treatment/prevention of venous thromboembolism. Oral anticoagulants include the vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs). The hemostasis laboratory plays a crucial role for the management of treated patients that spans from dose-adjustment based on laboratory testing that applies to VKAs to the measurement of drug concentrations in special situations that applies to DOACs. This article aims to overview how the hemostasis laboratory can help clinicians to manage patients on oral anticoagulants. Special interest is devoted to the international normalized ratio, used to manage patients on VKAs and to the measurement of DOAC concentrations, for which the role of the laboratory is still not very well defined and most interferences of DOACs with some of the most common hemostatic parameters are not widely appreciated.